2010
DOI: 10.1007/s00005-010-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Genes Encoding TGF-β1, TNF-α, and IL-6 Show Association with Type 1 Diabetes Mellitus in the Slovak Population

Abstract: Numerous cytokines have been shown to participate in the pathogenesis of type 1 diabetes (T1D). As gene polymorphisms can influence cytokine production or function, they may potentially contribute to genetic predisposition to the disease. The aim of this study was therefore to investigate the role of 22 single nucleotide polymorphisms (SNPs) in 13 cytokine and cytokine receptor genes in genetic susceptibility to T1D. Polymerase chain reaction with sequence-specific primers was used to genotype cytokine SNPs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
1
11
1
2
Order By: Relevance
“…An evaluation of the multiple polymorphisms in the TNF region revealed that these are in good fit with Hardy-Weinberg equilibrium in this population. In addition to the positive association of TNF Ϫ238G and/or TNF Ϫ308A alleles with T1D, as reported in other populations [37,45,50,51], we also observed a significant positive association of the TNFa5 allele in the North Indian population. The fact that TNF Ϫ308A allele is a "high expressor" allele [35,52] explains the immunological basis of its association with the inflammatory stage of pathogenesis of T1D to some extent.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An evaluation of the multiple polymorphisms in the TNF region revealed that these are in good fit with Hardy-Weinberg equilibrium in this population. In addition to the positive association of TNF Ϫ238G and/or TNF Ϫ308A alleles with T1D, as reported in other populations [37,45,50,51], we also observed a significant positive association of the TNFa5 allele in the North Indian population. The fact that TNF Ϫ308A allele is a "high expressor" allele [35,52] explains the immunological basis of its association with the inflammatory stage of pathogenesis of T1D to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…These results highlight possible populationbased variations in TNF association with T1D, although other factors that include discordance in study design, statistical evaluations, sample size, and methods of genotyping employed in different studies can also affect ethnic discrepancies. It has been suggested that the observed TNF association may indeed be caused by their LD with T1D-associated HLA class II alleles or haplotypes [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…In our study the frequencies of genotypes did not markedly differ from data previously reported in the literature (18)(19)(20). Contrasting with numerous reports on the frequencies of -308 G/A SNP and association with body adiposity and metabolic disturb- Table I.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have reported strong linkage disequilibriums between HLA DR3, HLA-DRB1*0301 alleles, and TNF-alpha-308 polymorphism [1,4], indicating that this significant association of TNF-alpha-308 polymorphism may not be independent. TNF-alpha-308 polymorphism might be only a participant in the whole genetic pathopoiesis of T1DM.…”
mentioning
confidence: 89%